Análise do controle tecnológico do concreto utilizado em obras na cidade de Pau dos Ferros/RN - Bezerra, Renata Ianca Dantas (Universidade Federal Rural do Semi-Árido, 2018)
In structural elements, one of the most important parameters for the dimensioning is the compressive strength of the concrete, as it directly influences several characteristics about its quality. For the determination of the compressive strength, so-called destructive or non-destructive tests can be used. This study performs the technological control of the concrete used in a work in the city of Pau dos Ferros / RN, as well as verifies the compressive strength of concrete applied in other works. For this, nine specimens were prepared, manually in the laboratory and produced concrete in the construction site, both through the same "optimal" feature proposed. The following tests were performed: slumptest and compressive strength for the concrete produced in the laboratory, and the sclerometry test for the concrete produced at the construction site, after the age of 21 days of cure. In the other works analyzed, a Checklist was applied and the sclerometry test was carried out on structural elements. The resistance of the concrete produced in the work reached the estimated result in a project of 25 MPa and the concrete produced in the laboratory presented a result of 27.62 MPa, better than expected in the project (25 MPa). Still, as for the other works analyzed, most of them do not have technological control in the production of their concretes, and as for the compressive strength, they present relatively low values, with an average of 15 MPa.
Keywords: Propriedades; Resistência à compressão; Esclerometria; Properties; compressive strength; Sclerometry; ENGENHARIAS::ENGENHARIA CIVIL